FAKTOR-FAKTOR YANG MENENTUKAN KEPUTUSAN PEMBELIAN SECARA ONLINE DI BUKALAPAK PADA MAHASISWA FAKULTAS EKONOMI UNDIKSHA - Made Abi Mantara; Ni Luh Wayan Sayang Telagawathi Telagawathi; Ni Nyoman Yulianthini (Fakultas Ekonomi Dan Bisnis Universitas Palangka Raya (UPR), 2022)
This study was aimed to examine (1) the factors that determine online purchasing decisions at Bukalapak, (2) the most dominant factor in determining online purchasing decisions at Bukalapak.The design of the study was quantitative research. The data was collected using a questionnaire followed by sampling with purposive sampling technique. The sampling technique is proportional sampling. The samples of this study are 231 respondents and tho so are analyzed by using factor analysis. The result of the study showed that (1) the factors that determine online purchasing decisions at Bukalapak is advantage factor of purchasing decision, product and marketing fix factor, social factor and culture factor, (2) the most dominant factor in determining online purchasing decisions at Bukalapak is advantage factor of buying decision which formed from factor of trust, security, comfort, convenience and risk.